2007
DOI: 10.1021/jf063735h
|View full text |Cite
|
Sign up to set email alerts
|

Melanoidins from Coffee Infusions. Fractionation, Chemical Characterization, and Effect of the Degree of Roast

Abstract: A method involving fractionation in ethanol aqueous solutions, anion exchange chromatography, and immobilized copper chelating chromatography was developed to obtain high molecular weight anionic melanoidin populations from coffee infusions. Six anionic fractions with different physicochemical properties (ethanol solubility and chelating ability) and chemical composition regarding carbohydrate as well as protein nature and content were isolated. Fractions with similar chemical composition were obtained for lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
159
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(182 citation statements)
references
References 57 publications
21
159
2
Order By: Relevance
“…Our study also showed the same phenomenon where the total phenolics increased with increasing initial pH of coconut neera and the end point temperature of heating. The presence of phenolic groups in the melanoidin fraction with high molecular weight has also been found in coffee brew due to the role of chlorogenic acid in the formation of melanoidin (Nunes and Coimbra, 2007;Bekedam et al, 2008).…”
Section: Total Phenolics Contentmentioning
confidence: 93%
“…Our study also showed the same phenomenon where the total phenolics increased with increasing initial pH of coconut neera and the end point temperature of heating. The presence of phenolic groups in the melanoidin fraction with high molecular weight has also been found in coffee brew due to the role of chlorogenic acid in the formation of melanoidin (Nunes and Coimbra, 2007;Bekedam et al, 2008).…”
Section: Total Phenolics Contentmentioning
confidence: 93%
“…is normally used to remove fatty compounds in coffee before extraction of antioxidants or other coffee compounds, such as melanoidins, (Bekedam et al, 2008a;Nunes & Coimbra, 2007;Ramalakshmi et al, 2009;Rufian-Henares & Morales, 2008). However, this process might influence on the antioxidant capacity of remained coffee samples because some organic antioxidants can be also removed.…”
Section: Influence Of Defatting and Lyophilization Defatting Processmentioning
confidence: 99%
“…In The absorbance at 420nm has been commonly used to characterize melanoidins, which are mainly originated by Maillard Reactions during roasting process of coffee and other heat-treated foods (Morales, 2005;Nunes & Coimbra, 2007). However, it has been reported that melanoidins accounted for only 65 % of color potency of the high molecular weight fraction obtained from light roasted coffee, and for only 39 % from dark roasted coffee (Nunes & Coimbra, 2007).…”
Section: Influence Of Torrefacto Roasting Process On Coffee Colormentioning
confidence: 99%
“…In The absorbance at 420nm has been commonly used to characterize melanoidins, which are mainly originated by Maillard Reactions during roasting process of coffee and other heat-treated foods (Morales, 2005;Nunes & Coimbra, 2007). However, it has been reported that melanoidins accounted for only 65 % of color potency of the high molecular weight fraction obtained from light roasted coffee, and for only 39 % from dark roasted coffee (Nunes & Coimbra, 2007). Many other brown-colored products appear to be sugar (retro)aldolization/dehydratation and carbohydrate condensation products, which may or may not be attached to proteins or other structures of amino nitrogen in a similar way to the Maillard Reactions (Rizzi, 1997;Hofmann, 1999).…”
Section: Influence Of Torrefacto Roasting Process On Coffee Colormentioning
confidence: 99%